The Moderation Effect of Job Autonomy on The Relationship Between Work Exhaustion and Chefs’ Job Satisfaction - Cankan, Murude Ertac; Elidemir, Servet Nasifoglu; Guden, Nafiya; Girgen, Mete (My University, 2025)
Research on job autonomy and job satisfaction is extensive across many fields, yet studies focusing specifically on chefs remain limited. Chefs face long and unsociable working hours, physically demanding tasks, time-pressured environments, and high levels of stress. These challenges have intensified since the Covid-19 pandemic, which caused widespread unemployment among chefs and heightened the need for creativity to attract customers. Such conditions contribute to work exhaustion, making job autonomy and job satisfaction crucial motivating factors in the profession. Guided by Self-Determination Theory (SDT), the sense of autonomy, competence, and relatedness plays an increasingly important role in strengthening chefs’ motivation. This study used a cross-sectional survey and regression analysis to examine how job autonomy influences the relationship between work exhaustion and job satisfaction among chefs working in four- and five-star hotels. Data were analysed through PLS-SEM using SmartPLS. The findings demonstrate that higher levels of job autonomy significantly enhance chefs’ job satisfaction, even under stressful working conditions.
Keywords: Hotels; Job satisfaction; Job autonomy; Chefs; Work exhaustion